2020
DOI: 10.4018/ijthi.2020010106
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Technology-based Reflective Practice Tools on Student Skill Development

Abstract: The purpose of this study was to examine how students received the combination of technology-based tools implemented in a staged manner within a curriculum and if any specific tool was of greater benefit in developing their reflective practice skills. Participants were 45 tertiary students enrolled in a health professional course. Qualitative and quantitative analysis revealed student preference for individual tools changed over time. Students preferred supportive tools (simulated video recordings, group blogg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In addition, the related research in this field usually focuses on the effect of reflective e-journals, while literature comparing the different modes of reflection remains lacking (Chan and Wong, 2021). Besides, the limited research about mode preference usually focused on fields of vocational training such as teacher training or medical training (Rolfe, 1997;Shoffner, 2009;Falk-Ross, 2012;O'Reilly and Milner, 2020), with little attention on the terrain of language acquisition. Another problem with research on reflection mode is that they often arrived at inconsistent findings.…”
Section: Reflection and Reflection Modementioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the related research in this field usually focuses on the effect of reflective e-journals, while literature comparing the different modes of reflection remains lacking (Chan and Wong, 2021). Besides, the limited research about mode preference usually focused on fields of vocational training such as teacher training or medical training (Rolfe, 1997;Shoffner, 2009;Falk-Ross, 2012;O'Reilly and Milner, 2020), with little attention on the terrain of language acquisition. Another problem with research on reflection mode is that they often arrived at inconsistent findings.…”
Section: Reflection and Reflection Modementioning
confidence: 99%
“…Another possible explanation for it might be the influence of age and learning stage as participants in this study were students majoring in English in the first year and their age differences were not distinct whereas participants in Cecilia's study involves students from Year 1 to Year 4. Previous studies reported that experienced learners may consider writing as a more effective way to reflect on oneself while novice learners may be more inclined to audio and video reflection (Bye et al, 2009;O'Reilly and Milner, 2020).…”
Section: Students' Preference For Reflection Modementioning
confidence: 99%
See 2 more Smart Citations
“…This research focuses only on SaaS based cloud services. SaaS cloud is defined as "application or function made available to customers, by the provider, through various devices like web browser or program interfaces" (Wease et al, 2018, p.449).The Software as a Service (SaaS) based cloud storage drives like Google Drive, iCloud, DropBox, Microsoft OneDrive, or Office 365, …etc., which are safe to store and access the data from anywhere, at any place without any complexity (Kalim et al, 2020, Chae, et al, 2020, Chege et al, 2020, Reilly and Milner, 2020, Sahu and Khandekar, 2020, Kani et al, 2020.…”
Section: Introductionmentioning
confidence: 99%